Long-Term Results in the Treatment of Avascular Necrosis of Femoral Head with Free Vascularized Fibular Graft - Bibi, Noshi; Mamoon Rashid; Sohail Hafeez; Saad ur Rehman; Haroon ur Rashid; Sakina Malik (Pakistan Armed Forces Medical Journal, 2023)
Objective: to evaluate outcomes of vascularized fibula flap used for Avascular necrosis of femoral head. Outcomes were recorded by post-operative Harris hip and radiological improvement of the femoral head.Study Design: Retrospective longitudinal study.Place and Duration of Study: Department of Plastic Surgery, Shifa International Hospital, Islamabad Pakistan, from Jan 2019 to Jan 2020.Methodology: Cases were recruited from 2005-2018 (SIH) performed by the same Orthopaedic and Plastic Surgeon. Data from 30 patients was reviewed. Ethical approval and consent of the patient were taken before the utilization of their data.Results: A total of 30 patients were included, comprising 27(90%) males and 3(10%) females. The mean age was 28.3± years. Pre-operative Harris Hip scores were fair in 17(56.7%) and poor in 13(43.3%) patients. Post operatively these scores improvedv and were noted to be excellent in 10(33.3%), good in 18(60%) and fair in 2(6,7%) patients. Radiological improvement was seen in 20(80%) patients, 8(23.3%) showed no change and 2(6.7%) went into progression. The radiological improvement was significantly associated with aetiology (p=0.004) and Avascular necrosis of HIP (p=0.007).Conclusion: A vascularized fibular graft is an effective treatment option for avascular necrosis of the femoral head in terms of improved radiological outcomes and post-operative Harris Hip scores.